National Reconviction Statistics and Studies in Europe = Nationale Rückfallstatistiken und -untersuchungen in Europa - Albrecht, Hans-Jörg; Jehle, Jörg-Martin (Universitätsverlag Göttingen, 2014)
Recidivism belongs to the main categories of criminology, crime policy and criminal justice. If the target of preventing offenders from reoffending is taken seriously crime policy should be measured by success of certain penal sanctions in terms of relapses. Also institutions that deal directly with crime and offenders need to get basic information on the consequences of their actions; particularly general knowledge about offender groups at risk of reoffending. All these are reasons why representative recidivism studies are needed. Meanwhile a lot of European countries gather systematic and comprehensive information on recidivism, periodically and on a national level. This volume presents an exemplary collection of such endeavors: Austria, Estonia, France, Germany, Switzerland and a comparative study of England and Wales, the Netherlands and Scotland.